2006
DOI: 10.1038/sj.ki.5001776
|View full text |Cite
|
Sign up to set email alerts
|

Tunneled catheters' outcome optimization among diabetics on dialysis through antibiotic-lock placement

Abstract: Efficacy and safety of antibiotic 'locks', in prevention of thrombotic and infectious complication-related morbidity and mortality, among diabetics dialyzed through tunneled-cuffed catheters (TCCs) has not been effectively investigated. This trial was designed to investigate the outcome of TCCs (n = 109), inserted among 96 diabetic end-stage renal disease patients (March 2002-February 2003), by comparing the catheter thrombosis, catheter-related bloodstream infections (CRBSI), catheter survival, and mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 25 publications
4
52
2
Order By: Relevance
“…The results are comparable to the outcomes reported in earlier trials involving antimicrobial locking solutions for the prevention of CRBSI among hemodialysis (HD) patients [6][7][8][9][10][11][12] (Fig. 1).…”
supporting
confidence: 79%
“…The results are comparable to the outcomes reported in earlier trials involving antimicrobial locking solutions for the prevention of CRBSI among hemodialysis (HD) patients [6][7][8][9][10][11][12] (Fig. 1).…”
supporting
confidence: 79%
“…These studies have been heterogeneous in nature and used different antibiotics (gentamicin, minocycline, cefazolin, cefotaxime, vancomycin) and nonantibiotic (citrate, taurolidine, EDTA) anti-microbial lock solutions; however, they have all shown a significant decline of 50 to 100% in CRIs compared with standard heparin lock without antibiotics or other sterilizing solutions (3). None of the aforementioned studies have reported anti-microbial resistance or loss of anti-microbial lock solution efficacy, but the longest follow-up period has only been 547 days in one study (13). Therefore, the emergence of bacterial antibiotic resistance from anti-microbial lock solutions and its potential complications remain to be determined.…”
mentioning
confidence: 91%
“…Numerous randomized, controlled trials (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), as well as meta-analyses of these studies (21)(22)(23)(24)(25), have been performed during the past decade to evaluate the benefit of anti-microbial lock solutions in chronic hemodialysis patients with TCCs. These studies have been heterogeneous in nature and used different antibiotics (gentamicin, minocycline, cefazolin, cefotaxime, vancomycin) and nonantibiotic (citrate, taurolidine, EDTA) anti-microbial lock solutions; however, they have all shown a significant decline of 50 to 100% in CRIs compared with standard heparin lock without antibiotics or other sterilizing solutions (3).…”
mentioning
confidence: 99%
“…Furthermore, two small randomized, controlled trials showed a reduction in mortality on crude analysis by use of a prophylactic antimicrobial lock solution (16,17). However, this approach has not been widely adopted.…”
Section: Introductionmentioning
confidence: 99%